2018
DOI: 10.1108/bfj-03-2018-0192
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional traffic light and self-regulatory consumption: the role of emotions

Abstract: Purpose The purpose of this paper is to analyse how the nutritional traffic light can reduce consumers’ intention to purchase unhealthy food by eliciting negative emotions (i.e. fear and guilt). The work also examines the moderating role of income in the above-mentioned relationships. Design/methodology/approach The empirical study was conducted in Ecuador. In an initial phase, exploratory research was carried out with two focus groups. Then a quasi-experiment was conducted with 330 participants following a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
(74 reference statements)
1
6
0
Order By: Relevance
“…The results are in line with Bruwer et al [38] regarding gender differences, but do not follow the same pattern for the age differences. In addition, the results of Sánchez-García et al [23] regarding the fact that female consumers are inclined to reduce the consumption of certain food products, in this case bread, are in line with our findings. Furthermore, a population-representative study might have different results.…”
Section: Influencing Factors Of Bakery Product Consumptionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results are in line with Bruwer et al [38] regarding gender differences, but do not follow the same pattern for the age differences. In addition, the results of Sánchez-García et al [23] regarding the fact that female consumers are inclined to reduce the consumption of certain food products, in this case bread, are in line with our findings. Furthermore, a population-representative study might have different results.…”
Section: Influencing Factors Of Bakery Product Consumptionsupporting
confidence: 93%
“…Consumers are also particularly interested in nutrition information on food labels [23,24]. In general terms, these labels also seek to inform and warn about nutritional content, facili-tating the choice of food and improving daily consumption [25].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The MTL was the most liked, trusted, quickest, and easiest to understand (Santos et al., 2020; Talati et al., 2016) and was effective in nutrient content estimation (Findling et al., 2018; Freire et al., 2017) across gender and age groups (Freire et al., 2017). A study conducted in Ecuador found that the green color evoked low levels of anxiety and guilt, while the red color evoked the opposite (Sanchez‐Garcia et al., 2019). In addition, income was found to have a moderating effect on the influence of color, as only high‐income participants reported increased anxiety and guilt in the face of yellow color, indicating caution as they transitioned from green to red.…”
Section: Fopl Effects On Consumer Behaviormentioning
confidence: 99%
“…Nudging reshapes the environment in which shoppers take their decisions by changing the presentation of options to consumers and making them more appealing, without removing options, changing economic incentive or constraining shoppers’ liberty of choice. In addition, the way companies communicate the healthiness of the products inside the store can change the effectiveness of a strategy since they can evoke different emotions that may affect judgements and behaviours (Sijtsema et al , 2009; Sánchez-García et al , 2018). In fact, several authors argued and demonstrated that emotions can influence customer satisfaction (Westbrook and Oliver, 1991) and customer loyalty (Yu and Dean, 2001).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%